Sickness Absenteeism and Dignity-based Management in the Industrial Processing Industry in Poland - Winnicka-Wejs, Alicja; Młokosiewicz, Marta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To present the findings from an empirical study conducted among employees in the industrial processing industry in Poland, examining sickness absenteeism and related absence behaviours as a part of dignity-based management.Research Design & Methods: The study was conducted through a survey questionnaire designed by the authors, utilising a diagnostic survey method. Data collection was facilitated by computer-assisted web interviewing (CAWI) and computer-assisted telephone interviewing (CATI). The analysis of survey results employed statistical methods, including chi-square tests, the Kruskal-Wallis test, and pairwise comparison through post hoc tests for significant correlations.Findings: More than half of the survey respondents acknowledged the occurrence of sickness absenteeism, defined as the abuse of sick leave in their organisations. This issue is closely linked to an organisation’s ability to inspire action among its employees, as well as to appreciate and support them. One in three respondents said they used sick leave as a retaliatory measure when annual leave requests were denied. The analysis also revealed differences in perceptions of absence behaviours among employees in the industrial processing industry. Larger companies experienced a higher incidence of unjustified sick leave compared to smaller and micro-sized ones, and medium-sized companies reported more instances than small companies.Implications / Recommendations: The findings from this study may prove useful for business owners, managers, and HR professionals who are dealing with issues of sickness absenteeism and dignity-based management. They can be used to build awareness of the determinants of employee absenteeism and the importance of dignity practices in management.Contribution: This article contributes to the body of knowledge in management and quality science, particularly in human resource management. It offers insights into the ethical analysis of work environment conditions, emphasising the importance of the moral principles in professional human relationships as a means of reducing the likelihood of workplace violations.